Extensão universitária Falar de Família é Familiar: trabalhando com as famílias em sua totalidade - Palucci, Claudia Mazzer Rodrigues [UNESP]; Liporoni, Andréia Aparecida Reis de Carvalho [UNESP]; Piana, Maria Cristina [UNESP]; Oliveira, Nayara Hakime Dutra [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
"Talking about Family is Family " is an extension project of the Auxiliary Unit Social Law Centre of the Faculty of Humanities and Social Sciences, UNESP , Campus of Franca / SP , which has the main objective of offering spaces for discussion and reflection on issues that pervade the daily family life. Holds monthly workshops with families of children from an early childhood institution . From the experiences of this extension , it emphasizes the importance of actions with references in search of spaces for discussion and reflection on the changes experienced within the current families as well as public policies that provide special attention to families , turning , above all, the guarantee of rights.

“Falar de Família é Familiar” é um projeto de extensão universitária da Unidade Auxiliar Centro Jurídico Social da Faculdade de Ciências Humanas e Sociais da UNESP, Câmpus de Franca/SP, que tem como objetivo principal o oferecimento de espaços de debates e reflexões sobre temáticas que perpassam o cotidiano familiar. Realiza oficinas mensais com as famílias de crianças de uma instituição de educação infantil. A partir das experiências desta extensão, enfatiza-se a importância de atuações com referenciais na busca de espaços para debates e reflexões sobre as mudanças vivenciadas no interior das famílias atuais, bem como nas políticas públicas que dispõem atenção especial às famílias, voltando-se, sobretudo, à garantia de direitos.
Keywords: Family; Children's education; Social; Community-institution relationship; Família; Educação infantil; Direitos sociais; Relação comunidade-instituição